PENGARUH FERMENTASI TERHADAP KANDUNGAN PROTEIN DAN KOMPOSISI ASAM AMINO DALAM SINGKONG - Almasyhuri Almasyhuri; Endi Ridwan; Heru Yuniarti; Hermana Hermana (Persagi, 1999)
Effects of Solid Fermentation on Protein Content and Amino Acid Composition of Cassava.This study was carried out to assess the protein and amino acid quantity of solid fermentation of cassava (Manihot esculenta) using pure culture of the Rhizopus oligosporus and traditional inoculum (laru). The protein content of the fermented product was analyzed by Biuret method, and the animo acid composition by HPLC (high performance liquid chromatography) method. The results showed that solid fermentation of cassava increased the protein content from 2.1% to 4.0% and 4.7%. The animo acid contents of the fermented product increased 2.5 folds of that of cassava. Higher increase was seen in substrates fermented with traditional inoculum. This is due to the addition of coconut oil and ammonium to the cassava substrate which improved the growth of mold.Key words: cassava (Manihot esculenta), food fermentation, protein content, amino acid composition